Effect of drying method on drying kinetics and flavonoid content of Chinese betel leaf (Peperomia pellucida L. Kunth) - Sutan, Sandra Malin; Nova, Diftiya; Yulianingsih, Rini (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Chinese betel is a weed that benefits health because of its antioxidant content. The drying process to obtain dried Chinese betel must be carried out using an adequate drying method, considering the antioxidant content in flavonoids sensitive to high temperatures. This research aimed to analyze the effect of drying methods - microwave, dehydrator, and oven - on drying characteristics, color, and flavonoid content and to obtain the best drying kinetics model for each drying method. Microwave drying was carried out at high and medium power while drying using a dehydrator and oven at 50 and 60℃. Drying using a microwave produces the lowest water content (1.36 – 2.29 %) and flavonoid content (7.12 – 7.53 QE/g), while using a dehydrator produces the highest water content (4.64 - 6.78 %) and flavonoid content (10.64 – 10.71 QE /g). Microwave drying produces the highest level of leaf color lightness, but the drying method did not affect the overall color change. The modified page drying model was most suitable for drying with a dehydrator, oven, and microwave at medium power, while the Handerson-Pabis model was suitable for drying kinetics using a microwave at high power.